Clinical utility of repeated rebiopsy for EGFR T790M mutation detection in non-small cell lung cancer - Lee, Eun Hye; Kwak, Se Hyun; Kim, Kyeong Yeon; Kim, Chi Young; Lee, Sang Hoon; Heo, Seok-Jae; Chang, Yoon Soo; Kim, Eun Young (Frontiers in Oncology, 2024)
Purpose: In cases where rebiopsy fails to find the epidermal growth factor receptor (EGFR) T790M mutation, the criteria for selecting patients for repeated rebiopsy remains unclear. This study aimed to assess the impact of repeated rebiopsy on T790M mutation detection in non-small cell lung cancer (NSCLC) patients. Methods: Patients with advanced EGFR-mutated NSCLC between January 2018 and December 2021 at three-referral hospitals in South Korea underwent retrospective review. Of 682 patients who had rebiopsy after disease progression, T790M mutation status was assessed in plasma circulating tumor DNA (ctDNA) and/or tumor tissues. Results: The overall T790M positivity rate increased from 40.8% after the first rebiopsy to 52.9% following multiple rebiopsies in the entire study population. Longer duration of initial EGFR TKI use (OR 1.792, ≥8 months vs. <8 months, p=0.004), better EGFR TKI responses (OR 1.611, complete or partial response vs. stable disease, p=0.006), presence of bone metastasis (OR 2.286, p<0.001) were correlated with higher T790M positivity. Longer EGFR TKI use and better responses increased T790M positivity in repeated tissue rebiopsy, while bone metastasis favored liquid rebiopsy. Additionally, T790M status has been shown to be positive over time through repeated rebiopsies ranging from several months to years, suggesting its dynamic nature. Conclusion: In this study, among patients who initially tested negative for T790M in rebiopsy, repeated rebiopsies uncovered an additional 23.5% T790M positivity. Particularly, it is suggested that repeated rebiopsies may be valuable for patients with prolonged EGFR TKI usage, better responses to treatment, and bone metastasis.